Ginzburg-Landau Vortices in Inhomogeneous Superconductors (Journal of Partial Differential Equations, 2002)
We study the vortex convergence for an inhomogeneous Ginzburg-Landau equation, -Δu = ∈^{-2}u(a(x) - |u|²), and prove that the vortices are attracted to the minimum point b of a(x) as ∈ → 0. Moreover, we show that there exists a subsequence ∈ → 0 such that u_∈ converges to u strongly in H¹_{loc}(\overline{Ω} \ {b}).